Revisiting the ESR chronology of the Early Pleistocene hominin occupation at Vallparadís (Barcelona, Spain). (2nd December 2015) - Duval, Mathieu; Bahain, Jean-Jacques; Falguères, Christophe; Garcia, Joan; Guilarte, Verónica; Grün, Rainer; Martínez, Kenneth; Moreno, Davinia; Shao, Qingfeng; Voinchet, Pierre
Abstract: ESR dating was applied to fossil teeth and optically bleached quartz grain samples from two units of the sequence at Vallparadís (Barcelona, Spain): weighted mean ESR age estimates of 858 ± 87 ka and 849 ± 48 ka were obtained for EVT-7, which includes the archaeological level 10, and EVT-8, respectively. These results are in good agreement with the existing magneto-biostratigraphic framework that constrain these deposits between 780 and 990 ka, and indicate that Vallparadís EVT-7 has a chronology very close to that of Atapuerca Gran Dolina TD-6 (Spain).